2015
DOI: 10.1074/jbc.m114.618736
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Mechanism of Stress-induced Translocation of 78-Kilodalton Glucose-regulated Protein (GRP78) to the Cell Surface

Abstract: Background: ER stress induces cell surface translocation of GRP78/BiP. Results: GRP78 translocation to the cell surface requires its substrate binding domain and exists majorly as a peripheral protein.Conclusion: GRP78 anchors on the cell surface via interaction with other proteins, and the translocation mechanism is cell context-dependent. Significance: Learning how GRP78 exists on the cell surface is crucial for understanding its signaling regulatory functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
148
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(159 citation statements)
references
References 58 publications
9
148
1
1
Order By: Relevance
“…Alternately, while GRP78 is involved in JEV binding, MHC-I may be involved in virus internalization, similar to what has been reported for coxsackievirus A9 (27). A recent study has shown that GRP78 anchors on the cell membrane via interactions with other proteins and that its translocation mechanism is cell context dependent (38). GRP78 has been reported to interact with diverse proteins, such as voltage-dependent anion channel (46) and the DnaJ-like protein MTJ-1 (28).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Alternately, while GRP78 is involved in JEV binding, MHC-I may be involved in virus internalization, similar to what has been reported for coxsackievirus A9 (27). A recent study has shown that GRP78 anchors on the cell membrane via interactions with other proteins and that its translocation mechanism is cell context dependent (38). GRP78 has been reported to interact with diverse proteins, such as voltage-dependent anion channel (46) and the DnaJ-like protein MTJ-1 (28).…”
Section: Discussionmentioning
confidence: 74%
“…GRP78 localization on the cell membrane occurs via interactions with other proteins, and its translocation mechanism is cell type dependent (38). The protein has been shown to be a part of the receptor complex, along with major histocompatibility class I (MHC-I) for coxsackievirus A9 entry (27).…”
Section: Resultsmentioning
confidence: 99%
“…Although GRP78 translocation have been studied mainly in cancer cell lines and have been found to be cell context-dependent (Tsai et al, 2015), there exist some common details for its mechanism of action. GRP78 can be translocated and anchored to the cell surface by binding to the ER-co-chaperone HTJ-1/MTJ-1 (Birukova et al, 2014; Figure 1).…”
Section: Grp78 a Very Important Protein With Multiple Functions In Mmentioning
confidence: 99%
“…A recent study using a combination of biochemical, mutational, FACS, and single molecule super-resolution imaging approaches, reports that GRP78 mainly exists as a peripheral protein on plasma membrane via interaction with other cell surface proteins including glycosylphos-phatidylinositol-anchored proteins since it lacks a true transmembrane domain (Tsai et al, 2015). In addition, the authors discovered that cell-surface GRP78 expression requires its substrate binding activity but is independent of ATP binding.…”
Section: Grp78 a Very Important Protein With Multiple Functions In Mmentioning
confidence: 99%
“…Only the spliced form of XBP-1 protein is an active transcription factor (50). Moreover, it was demonstrated that GRP78 is implicated in the cellular trafficking, because it is able to translocate to the cell surface (51). Thus, to better understand the effects of glucose deprivation on NEU3, cells were cultured under high glucose concentration (which is the standard condition normally used to culture cells) and normo-and low glucose concentration.…”
Section: Neu3 Sialidase Protein Interactorsmentioning
confidence: 99%